YOUTH EMPOWERMENT THROUGH DIGITAL BRANDING AND MARKETING FOR PROBLEM SOLVING OF FARMERS IN TALUNREJO VILLAGE: PEMBERDAYAAN PEMUDA MELALUI DIGITAL BRANDING DAN MARKETING UNTUK PROBLEM SOLVING PARA PETANI DI DESA TALUNREJO - Rohmatillah, Alfin; Laila Arisandra, Martha; Zulkarnaen, Have (Antis-publisher, 2024)
This article describes the challenges faced by tobacco farmers in Talunrejo Village, Lamongan, related to problems regarding modern marketing. Lack of knowledge about this matter results in limited access to marketing products more widely. Young farmers in this village as the next generation of agriculture and the economy are invited to participate in further marketing improvements. In an effort to overcome this problem, you can implement a strategy for creating digital branding and digital marketing through social media in the form of Facebook and Instagram. This research contributes to the understanding of youth empowerment through digital branding and marketing to overcome tobacco farming problems and provides insight into solutions that can be implemented to increase farmer productivity and welfare.